Combined 18F-FDG-PET and diffusion tensor imaging in mesial temporal lobe epilepsy with hippocampal sclerosis - Javier Aparicio; Mar Carreño; Núria Bargalló; Xavier Setoain; Sebastià Rubí; Jordi Rumià; Carles Falcón; Anna Calvo; Berta Martí-Fuster; Nelly Padilla; Teresa Boget; Luís Pintor; et al. (NeuroImage: Clinical, 2016)
Objectives: Several studies using 18F-fluorodeoxyglucose positron emission tomography (18F-FDG-PET) or diffusion tensor imaging (DTI) have found both temporal and extratemporal abnormalities in patients with mesial temporal lobe epilepsy with ipsilateral hippocampal sclerosis (MTLE-HS), but data are lacking about the findings of both techniques in the same patients. We aimed to determine whether the extent of 18F-FDG-PET hypometabolism is related to DTI abnormalities. Methods: Twenty-one patients with MTLE-HS underwent comprehensive preoperative evaluation; 18 (86%) of these underwent epilepsy surgery. We analyzed and compared the pattern of white matter (WM) alterations on DTI and cortical hypometabolism on 18F-FDG-PET. Results: We found widespread temporal and extratemporal 18F-FDG-PET and DTI abnormalities. Patterns of WM abnormalities and cortical glucose hypometabolism involved similar brain regions, being more extensive in the left than the right MTLE-HS. We classified patients into three groups according to temporal 18F-FDG-PET patterns: hypometabolism restricted to the anterior third (n = 7), hypometabolism extending to the middle third (n = 7), and hypometabolism extending to the posterior third (n = 7). Patients with anterior temporal hypometabolism showed DTI abnormalities in anterior association and commissural tracts while patients with posterior hypometabolism showed WM alterations in anterior and posterior tracts. Conclusions: Patients with MTLE-HS have widespread metabolic and microstructural abnormalities that involve similar regions. The distribution patterns of these gray and white matter abnormalities differ between patients with left or right MTLE, but also with the extent of the 18F-FDG-PET hypometabolism along the epileptogenic temporal lobe. These findings suggest a variable network involvement among patients with MTLE-HS.